Key papers on borderline disorders : with IJP internet discussion reviews - Williams, Paul, D.P.M (International journal of psychoanalysis key papers series., 2002)
This particular collection of papers has been given a contemporary edge with the inclusion of concurrent international online discussions of the papers. These lively debates serve to contextualise these important intellectual contributions to the world of psychoanalysis.